Affects as Mediators of the Negative Effects of Discrimination on Psychological Well-Being in the Migrant Population - Urzúa, Alfonso; Henríquez, Diego; Caqueo-Urízar, Alejandra (Frontiers in Psychology, 2020)
There is abundant empirical evidence on the negative effects of discrimination on psychological well-being. However, little research has focused on exploring the factors that can mitigate this effect. Within this framework, the present study examined the mediating role of positive and negative affects in the relationship between ethnic and racial discrimination and psychological well-being in the migrant population. About 919 Colombians, first-generation migrants, residing in Chile (Arica, Antofagasta, and Santiago) were evaluated, of which 50.5% were women, and the participants’ average age was 35 years (range: 18–65 years). Krieger’s discrimination questionnaires, Watson’s Positive and Negative Affect Schedule (PANAS), and Ryff’s Psychological Well-Being Scale were applied. The measurement models of each variable were estimated, and then the structural equation models were used. The results of the hypothesized multiple mediation model showed that the main mediator in the relationship between ethnic-racial discrimination and psychological well-being was positive affects over negative ones.